Three fools and a horse - Baker, Betty; Rounds, Glen 1906-. (New York Macmillan, 1975)
A retelling of three traditional Apache tales about the nonsensical adventures of the Foolish People.
Keywords: Indians of North America -- Southwest, New -- Folklore; Apache Indians -- Folklore; Apache Indians -- Folklore; Indians of North America -- Folklore